Analysis on differences and influencing factors of economic development in counties of Guangxi Zhuang Autonomous Region - Sun, Changsheng; Hu, Xinqi; Zhang, Chunying; Wu, You (Zhejiang da xue xue bao. Journal of Zhejiang University. Sciences edition. Li xue ban, 2023)
The unbalanced economic development is a normal state of regional economy, and moderate regional economic differences are conducive to exerting regional comparative advantages. In recent years, the research work on regional economic differences are mostly concentrated in the developed areas such as the central coastal areas, the Yangtze River Delta and the Pearl River Delta, and there are few research results concerning the underdeveloped areas such as Guangxi. Taking 92 counties in Guangxi Zhuang Autonomous Region as the basic research objects, this paper uses the coefficient of variation, theil index and exploratory spatial data analysis to study the spatial and temporal evolution pattern of county agglomeration differences in Guangxi from 2005 to 2020, and explores the causes of this difference by constructing the spatial Durbin model. The results show that:（1） the absolute difference of county economy in Guangxi increased in this period, while the relative difference decreased slightly, and the intra-regi